Phytochemical identification and in silico study of ethanolic extract of white cabbage as a phosphodiesterase 1B inhibitor - Nazir Ahmad; Kaisun Nesa Lesa; Navista Sri Octa Ujiantari; Ari Sudarmanto; Zullies Ikawati; Nanang Fakhrudin (Shahrekord University of Medical Sciences, 2023)
Introduction: Memory dysfunction has remained a challenging issue globally. Nootropics have proven fruitful in managing cognitive dysfunction but because of their side effects, opportunities exist to explore alternatives. White cabbage is a cost-effective natural source of phytochemicals without side effects and has remained uninvestigated as a nootropic agent. This study sought to identify secondary metabolites in white cabbage extract (WCE) and to predict the molecular interaction between the phytochemical constituents of cabbage and phosphodiesterase-1B (PDE1B) using in silico studies. Methods: The WCE was prepared by macerating crushed fresh white cabbage with ethanol for 24 h with continuous stirring. The phytochemical profile of WCE was analyzed using thin layer chromatography (TLC)-densitometry, and molecular docking studies were performed to predict the underlying mechanism action of the phytochemicals with PDE1B. Results: The TLC-densitometry analysis showed that WCE was a rich source of sinigrin, whereas quercetin, chlorogenic acid, and rutin were not detected. In silico studies identified neobrassicin as having the highest affinity (∆Gbind: −19.3358 kcal/mol) for PDE1B. However, quercetin (∆Gbind: −13.1813 kcal/mol) and chlorogenic acid (∆Gbind: −14.8706 kcal/mol) exhibited moderate interaction with PDE1B. Conclusion: These results suggest that WCE has the potency to improve memory function by blocking PDE1B, and this preliminary study implies upcoming in vitro and in vivo research.